Epidemiology, risk factors and varroa mite control in the Estonian honey bee population. Issue 5 (5th December 2016) - Mõtus, Kerli; Raie, Arvi; Orro, Toomas; Chauzat, Marie-Pierre; Viltrop, Arvo
Abstract : This is the first large scale study demonstrating the status of varroa infestation and control and related risk factors in Estonian apiaries. Colonies in one hundred and ninety-six apiaries were sampled during 2012–2013. A questionnaire was used to record management, as well as treatment procedures applied. The majority of apiaries sampled (98.5, 95% CI = 95.6; 99.7%) were infested with varroa mites and the mean proportion of affected colonies within apiaries was high (78.9, 95% CI 77.2; 80.6%). Apiary median colony infestation level was 2 mites per 300 bees (mean 4.5, range 0–25). According to multivariable random-effect logistic regression analysis, the numbers of colonies in an apiary (OR = 1.04, 95% CI 1.01; 1.06, p = 0.004) and the presence of a hybrid breed of bees (OR = 2.22, 95% CI 0.88; 5.61, p = 0.093) were associated with higher risk of colony varroa infestation. Apiary management by a professional beekeeper (OR = 0.38, 95% CI 0.15; 0.97, p = 0.044), bees of the Buckfast breed (OR = 0.36, 95% CI 0.11; 1.13, p = 0.079), synchronized treatments between neighboring beekeepers (OR = 0.34, 95% CI 0.16; 0.68, p = 0.003) and the presence of farmland around the apiary (OR = 0.29, 95% CI 0.09; 0.95, p = 0.041) were factors protective against colony varroa infestation. Varroa treatment was applied in 93% of the studied apiaries. Chemical and organic substances were used by 66 and 61% of beekeepers, respectively in 2012.